PERLINDUNGAN HUKUM HAK ULAYAT MASYARAKAT ADAT DI INDONESIA PERSPEKTIF PERBANDINGAN DENGAN NEGARA LAIN - Ibnusani, Rijal (Fakultas Hukum, Universitas Islam Balitar, 2025)
Abstract This research comprehensively analyzes the legal protection of Indigenous Communal Land Rights (Hak Ulayat) in Indonesia and compares it with implementation mechanisms in Malaysia and Australia. The primary goal is to formulate an ideal institutional model for protecting Hak Ulayat in Indonesia, drawing upon best practices from Australia. The approach used is normative juridical, primarily employing comparative legal analysis and statutory review. The findings indicate that while Indonesia formally recognizes Hak Ulayat (UUD 1945 and UUPA 1960), practical protection is hampered by overlapping regulations, conflicts of interest (state-corporate), and administrative weaknesses. Comparatively, Malaysia grants formal legal status (Native Customary Rights/NCR) but maintains dominant state control. In contrast, Australia, through the Native Title Act 1993, offers a system that is more structured, participatory, and provides stronger legal certainty. The conclusion asserts that Indonesia urgently requires regulatory and institutional reform. The ideal institutional model, achievable through comparative learning, must involve an independent body that synergizes with the formal institution (BPN) to ensure more effective, just, and transparent protection of Indigenous Communal Land Rights.